2017
DOI: 10.1016/j.otsr.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term assessment of meniscal extrusion after meniscal repair

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…2 On injury, the meniscus often becomes displaced from its physiological position and extrudes from the tibial plateau 5,6,18 ; as such, meniscal extrusion/translation can be one of the features of a torn meniscus on magnetic resonance imaging (MRI) scans. 1,9,20,31 Liu et al 21 showed that displacement of the LM was associated with the occurrence of symptomatic osteoarthritis, but few other studies have investigated the relationship between extrusion of the LM and osteoarthritis in the clinical setting. In addition, any relationship between meniscal displacement and the degree of meniscal tear or load-transmission function of the LM remains unclear.…”
mentioning
confidence: 99%
“…2 On injury, the meniscus often becomes displaced from its physiological position and extrudes from the tibial plateau 5,6,18 ; as such, meniscal extrusion/translation can be one of the features of a torn meniscus on magnetic resonance imaging (MRI) scans. 1,9,20,31 Liu et al 21 showed that displacement of the LM was associated with the occurrence of symptomatic osteoarthritis, but few other studies have investigated the relationship between extrusion of the LM and osteoarthritis in the clinical setting. In addition, any relationship between meniscal displacement and the degree of meniscal tear or load-transmission function of the LM remains unclear.…”
mentioning
confidence: 99%
“…While the suture anchor repair typically involves an all-inside technique with a suture anchor and additional sutures secured at the root attachment, the transtibial approach involves drilling a tunnel through the tibia to the native root attachment, shuttling sutures that are cinched to the torn meniscus through the tunnel, and then securing the sutures to the anterior aspect of the tibia 66,69,70 . Small case-control and cohort studies have demonstrated favorable clinical outcomes following meniscal repair utilizing either repair method, although the persistence and progression of extrusion remains a risk 66,69,71-75 . The transtibial approach is preferred by the senior author (B.J.C.)…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…With the improvements in CT [18] and MRI scanning [19], have been shown to improve diagnostic accuracy in many knee disorder. MRI scanning is first choice for diagnosis of meniscus tear rarely use of arthrograph.…”
Section: Imagingmentioning
confidence: 99%